Pelaksanaan Pernyataan Standar Akuntansi Pemerintah No. 13 (PSAP 13) tentang Penyajian Laporan Keuangan Badan Layanan Umum di Perguruan Tinggi Negeri (Studi pada Badan Layanan Umum Universitas Brawijaya) - Wartini, Martha; Saleh, Choirul; Domai, Tjahjanulin (Jurnal Ilmiah Administrasi Publik, 2020)
Higher Education carries the obligation to improve the competitiveness of the nation through increasing the intellectuality of the nation's successors. Excellent service must be given in order to achieve the vision and mission in improving the quality of education. University autonomy is needed to create more flexible institutional management. One of the autonomy models is the Public Service Agency (BLU). In carrying out its duties, the BLU must use a special pattern in the presentation of its financial statements. The Government Accounting Standards Statement (PSAP) 13 is used to simplify BLU financial reporting. The implementation of PSAP 13 at Universitas Brawijaya was discussed in this study to give an idea of how it was implemented in the Public Service Agency.